A 142 W Ho:YAG laser single-end-pumped by a Tm-doped fiber laser at 1931 nm. (4th October 2019) - Yao, W C; Li, E H; Shen, Y J; Ren, C Y; Zhao, Y G; Tang, D Y; Shen, D Y
Abstract: In this paper, a high-power Ho:YAG laser in-band pumped by a Tm-doped fiber laser at 1931 nm is reported. A maximum output power of 142.2 W is achieved at 2091 nm using a single-end-pumped configuration, corresponding to a slope efficiency of 56.7%. This is, to the best of our knowledge, the highest output power directly generated by bulk Ho-oscillators in the 2.1 µ m spectral region.